The impact of InsurTech on advancing sustainable specialty agricultural product insurance in China - Hou, Dainan; Wang, Xin (Frontiers in Sustainable Food Systems, 2024)
The development of specialized agricultural product insurance is crucial for perfecting China’s agricultural insurance system and promoting rural revitalization. Currently, specialized agricultural product insurance in China faces numerous challenges in key areas such as rate determination, risk assessment, and loss adjustment, which have become bottlenecks restricting its sustainable development. This paper explores how insurance technology (InsurTech) can enhance the ecological system of specialized agricultural product insurance through technological innovation and overcome these industry pain points. It elaborates on how InsurTech can enhance farmers’ interactive experience and satisfaction, improve the management efficiency of insurance companies, strengthen government regulation, and promote the sustainable development of the insurance business. Moreover, this study deeply analyzes the practical barriers in implementing InsurTech and proposes corresponding strategies, including establishing innovative incentive mechanisms, improving relevant policies and regulations, building a multidimensional data platform to achieve data interoperability, and strengthening the construction of digital rural infrastructure to enhance farmers’ technological literacy, thereby advancing the sustainable development of InsurTech in specialized agricultural product insurance.